Elaboração de questionário para aferir concepções sobre inclusão de aluno com deficiência em aulas de educação física - Fiorini, Maria Luiza Salzani [UNESP]; Manzini, Eduardo José [UNESP] (My University, 2014)
The natural elapse of physical education classes does not seem to be so tranquil when the teacher is faced with students with and without disabilities in the same class. This way it is appropriate to disclose how the teacher understands the practice by itself, before the educational inclusion of the students with disabilities. It was developed a questionnaire to gauge conceptions on the inclusion of students with disabilities in physical education, through six steps: 1) performance of a semi-structured interview, 2) preparation of the first version of the questionnaire, 3) assessment of the utterances by judges and 4) writing of the second version; 5) a test to assess the clearness, and the understanding of the utterances; 6) the preparation of the third version of the questionnaire.

O transcorrer habitual das aulas de Educação Física parece não ser tão tranquilo quando o professor defronta-se com alunos com e sem deficiência na mesma turma. Faz-se cabível, então, revelar como o professor entende, a própria prática, diante da inclusão educacional de alunos com deficiência. Elaborou-se um questionário para aferir concepções sobre a inclusão de alunos com deficiência na Educação Física, por meio de seis etapas: 1) realização de entrevista semiestruturada; 2) elaboração da primeira versão a partir das entrevistas; 3) avaliação dos enunciados por juízes; 4) redação da segunda versão; 5) teste para avaliar a clareza e o entendimento dos enunciados; 6) elaboração da terceira versão do questionário.
Questionnaire elaboration to gauge conceptions on inclusion of student with disabilities in physical education classes
Keywords: Educacao Especial; Concepção de deficiencia; avaliação